Shoot growth of Merlot and Cabernet Sauvignon grapevine varieties - Borghezan, Marcelo; Gavioli, Olavo; Vieira, Hamilton Justino; Silva, Aparecido Lima da (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate shoot growth of the grapevine varieties Merlot and Cabernet Sauvignon, during 2006/2007, and Cabernet Sauvignon, during 2008/2009, in São Joaquim, SC, Brazil. The experiment was carried out in a commercial vineyard trained on a vertical trellis system. The shoots of the central part of the plants were selected, and the lengths from the base to the apex of 20 shoots per cultivar were evaluated. In 2006/2007, monitoring began at pruning, on 9/15/2006, and ended on 2/6/2007, totalizing144 days of evaluation. During the 2008/2009 cycle, phenology and shoot growth for 'Cabernet Sauvignon' were assessed from grape development (1/13/2009) (pea‑sized grapes) until shoot vegetative growth had ceased. Budburst occurred in the second half of September, and shoot‑growth cessation occurred during ripening. Higher growth rates (about 4 cm per day) were observed in pre‑ and post‑flowering, followed by reduction due to the competition for photosynthates for the formation of flowers and bunches. Temperature and photoperiod induce grapevine shoots to cease growth in the highland regions of Santa Catarina State, Brazil.